Removal of Hazardous Oxyanion Pollutants by Lanthanum (Iii) Hydroxide and Lanthanum (III) - Loaded Ion Exchangers - Ahmed, Yehya M. (2004)
La(III) loaded poly(hydroxamic acid) chelating resin (LaPHA), lanthanum hydroxideloaded poly(hydroxamic acid) chelating resin (LaOHPHA) and lanthanum hydroxide (La(OH)3) were prepared and evaluated as sorbents for removal of As(V), As(III) and Cr(VI) from aqueous solution. LaPHA was prepared by loading lanthanum(III) onto PHA resin which was prepared by the reaction of PMA with hydroxyl amine hydrochloride in alkaline medium. LaOHPHA was prepared by treating LaPHA with ammonia solution and La(OH)3 was prepared by neutralizing LaCl3 solution with ammonia solution. In order to understand the sorption characteristics of As(V), As(III) and Cr(VI) by the sorbents, batch and column studied were performed under various experimental conditions. The parameters studied were pH, contact time, isotherm study, iv temperature, sorbent dosage, presence of competitive anions, flow rate, sorptiondesorption study and industrial wastewater treatment. The results of batch study indicated that the sorption process was pH dependent and endothermic. Kinetic study showed that uptake of As(V) ion by all of the sorbents reached equilibrium after about 15 hours and about 10 hours for Cr(VI) by La(OH)3. The maximum sorption capacity of LaPHA for As(V) at room temperature determined from the Langmuir isotherm was 14.8 mg-As/g-sorbent compared to that of LaOHPHA for As(V) which was 17.7 mg-As/g-sorbent, while the maximum sorption capacity of La(OH)3 for As(V) was 133.3 mg-As/g-sorbent and for Cr(VI) was 33.1 mg-Cr/g-sorbent. The results also showed that the La(OH)3 in the PHA resin (LaOHPHA) was more stable in acidic medium compared to the La(OH)3. The uptake increased with increasing sorbent dosage and also increased by increasing in temperature. In the presence of competitive ions, metal uptake decreased and it was found that phosphate ion is the most effective one. In desorption study, As(V) could be removed almost quantitatively from LaPHA and LaOHPHA by eluting with 0.4M and 0.2M NaOH solutions, respectively. The column with LaPHA could be used for not more than 3 cycles and 2 cycles for LaOHPHA. Both LaPHA and LaOHPHA resins were found effective to remove arsenic from wastewater samples from wood treatment industry. The percentages of arsenic removal from wastewater by the sorbents were higher for lower v concentrations samples. More than 90% removal was obtained from the sample with the lowest arsenic concentration.